Molecular simulation for piperazinium based ILS: Effects of alkyl chain, concentration and anions on Henryâs constants - Babiker, O.E. (Trans Tech Publications Ltd, 2014)
a simulation study of molecule structuring, electrons density polarization (Ï-profile) and Henryâs law constant (HLC) have been achieved for three of the dual charge cation ionic liquids (DCCILs) specifically, 1, 4-di-(butyl, hexyl, Octyl)-1, 4-dimethyl-piperazinium using COSMO-RS molecular dynamic software. The electron density chart indicates the ability of the DCCILs to interact with the polar groups (H-bond donor) which was presented the strong peak in (-1.2Ã10-2) e/Çº2. The DCCILs also showed a strong peaks to interact with the non-polar groups which are located at (-0.2Ã10-2) e/Çº2). The screening of the selected anions showed a significant deferens in predicted Henryâs constant values. The BF4- anion presented the greatest HLC values followed by NO3-, Br- PF6- and finally the octylsulfate - as lowest HLC values. The increases of DCCILs concentration always use to decrease the HLC values for all presented anions. The outcomes of this work were systematically pointed to the possibility of DCCILS solubility in water. In addition the study identified and classified the selected anions and the cation alkyl chain in terms of their contribution to improve the CO2 solubility in DCCILs. Â© 2014 Trans Tech Publications, Switzerland.